Soluble PD-1: Predictive, Prognostic, and Therapeutic Value for Cancer Immunotherapy - Khan, Muhammad; Zhao, Zhihong; Arooj, Sumbal; Fu, Yuxiang; Liao, Guixiang (Frontiers in Immunology, 2020)
Programmed death protein 1 (PD-1) interaction with PD-L1 deliver immunosuppressive environment for tumor growth, and its blockade with directed monoclonal antibodies (anti-PD-1/anti-PD-L1) has shown remarkable clinical outcome. Lately, their soluble counterparts, sPD-1 and sPD-L1, have been detected in plasma, and elevated levels have been associated with advanced disease, clinical stages, and worst prognosis for cancer patients. Elevated plasma levels of sPD-L1 have been correlated with worst prognosis in several studies and has displayed a persistent outlook. On the other hand, sPD-1 levels have been inconsistent in their predictive and prognostic ability. Pretherapeutic higher sPD-1 plasma levels have shown to predict advanced disease state and to a lesser extent worst prognosis. Any increase in sPD-1 plasma level post therapeutically have been correlated with improved survival for various cancers. In vitro and in vivo studies have shown sPD-1 ability to bind PD-L1 and PD-L2 and block PD-1/PD-L1 interaction. Local delivery of sPD-1 in cancer tumor microenvironment through local gene therapy have demonstrated an increase in tumor specific CD8+ T cell immunity and tumor growth reduction. It had also exhibited enhancement of T cell immunity induced by vaccination and other gene therapeutic agents. Furthermore, it may also lessen the inhibitory effect of circulating sPD-L1 and enhance the effects of mAb based immunotherapy. In this review, we highlight various aspects of sPD-1 role in cancer prediction, prognosis, and anti-cancer immunity, as well as, its therapeutic value for local gene therapy or systemic immunotherapy in blocking the PD-1 and PD-L1 checkpoint interactions.